Pengaruh Profitabilitas Terhadap Nilai Perusahaan dengan Pengungkapan CSR sebagai variabel Moderasi (Perusahaan yang tergabung di JII dan Indeks SRI-KEHATI periode 2016-2018) - Niswatin Chasanah; Sylva Alif Rusmita (Universitas Airlangga, 2019)
This study aims to determine and analyze the effect of profitability (ROA) on stock prices with corporate social responsibility (CSR) as a variable that moderates the two variables. The object of this research is companies incorporated in JII and SRI-KEHATI indexes that meet the test sample criteria during the period 2016 - 2018. This study uses a quantitative approach. Analysis of the data in this study used a moderation regression analysis (MRA). This study uses 20 samples for the JII index and 21 for the SRI-KEHATI index. Data obtained from the company's financial statements incorporated in JII and the SRI-KEHATI index for the period of 2016 - 2018 on the Indonesia Stock Exchange (IDX) website. The results showed that Return On Assets (ROA) had a significant effect on JII stock prices and SRI-KEHATI index stock prices. Furthermore, with CSR as a moderating variable showing the results of research with JII that is partially CSR disclosure shows a significant value which means CSR disclosure is able to moderate the relationship of ROA with JII stock prices. Overall (simultaneous) independent variables (ROA, CSR, ROA * CSR) significantly influence the stock price of JII. Furthermore, the results of research with the SRI-KEHATI index partially disclose CSR as a moderating variable showing a significant value. This means that CSR disclosure is not able to moderate the relationship of ROA with JII stock prices. while overall (simultaneous) independent variables (ROA, CSR, ROA * CSR) affect the stock price of the SRI-KEHATI index.Keywords: Profitability,StockPrice,ROA,CSR